Simultaneous selection of eucalyptus clones based on yield, stability and adaptability - Rosado, Antônio Marcos; Rosado, Tatiana Barbosa; Alves, Alexandre Alonso; Laviola, Bruno Galvêas; Bhering, Leonardo Lopes (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate genetic parameters and to determine the efficiency of the simultaneous selection of eucalyptus clones based on yield, stability, and adaptability. Twenty‑one clones, with 36 months of age, from the genetic breeding program of the company Cenibra were used. The experiment was done in a randomized complete block design, in four environments, with 21 replicates of one plant per plot. The clones were evaluated as to the variables: diameter at breast height, plant height, and total volume with bark. The genetic parameters were estimated using the mixed model procedure (REML/BLUP), and selection was based on the harmonic mean of the relative performance of the genetic values (HMRPGV), with three strategies: selection based on the predicted genetic gain, considering the average performance of genotypes in all environments (without interaction effect) or the performance on each environment (with interaction effect); and simultaneous selection based on productivity, stability, and adaptability. Environment particularities influenced the phenotypic expression of the clones. The heritability estimates indicated good perspectives for selecting clones with high yield, stability, and adaptability. Simultaneous selection optimizes clone selection and can be used in the construction of breeding populations and in the recommendation of genetic materials for commercial plantations.